2021
DOI: 10.1097/ta.0000000000003488
|View full text |Cite
|
Sign up to set email alerts
|

Damage-control surgery in patients with nontraumatic abdominal emergencies: A systematic review and meta-analysis

Abstract: BACKGROUNDAfter the successful implementation in trauma, damage-control surgery (DCS) is being increasingly used in patients with nontraumatic emergencies. However, the role of DCS in the nontrauma setting is not well defined. The aim of this study was to investigate the effect of DCS on mortality in patients with nontraumatic abdominal emergencies.METHODSSystematic literature search was done using PubMed. Original articles addressing nontrauma DCS were included. Two meta-analyses were performed, comparing (1)… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…A systematic review and meta-analysis of patients with non-trauma abdominal emergencies reported no difference regarding mortality between DCS or conventional management. However, the analysis used studies that compared observed and expected mortality, with a lower rate of observed mortality in patients with DCS [ 55 ].…”
Section: Resultsmentioning
confidence: 99%
“…A systematic review and meta-analysis of patients with non-trauma abdominal emergencies reported no difference regarding mortality between DCS or conventional management. However, the analysis used studies that compared observed and expected mortality, with a lower rate of observed mortality in patients with DCS [ 55 ].…”
Section: Resultsmentioning
confidence: 99%
“…Internationally, the use of DCS in non‐trauma emergencies has been reported as being used with great variety, but usually to a wider extent (8–25%) than we presented here [21, 23]. A recent meta‐analysis found no difference in mortality in patients undergoing non‐trauma DCS compared to conventional surgery [24]. The WSES guidelines [17] recommend considering open abdomen treatment following surgical management of acute mesenteric ischemia and abdominal compartment syndrome, but also urges caution when applying DCS on wider indications.…”
Section: Discussionmentioning
confidence: 67%
“…Adding to the risk of SSI, a contaminated abdomen is typically found in patients undergoing laparotomy for abdominal emergencies, which was identified as an independent predictor for SSI, too. To overcome SSI in presence of IPOM, damage-control surgery principles with delayed abdominal closure may help to reduce the rate of SSI in this group of patients [ 23 ]. However, in selected cases, the benefits of IPOM placement, such as definitive abdominal closure, outweigh the risk for SSI and may be the only available treatment option.…”
Section: Discussionmentioning
confidence: 99%